Correlation Between Heat Stress With Dehydration Incident Among Outdoor Workers at Parking Area and Security in a Private Hospital in Palembang - Artanto, Ardi; Putra Gunawan, Ernes; Luthfiyah Fadilah, Dennisa (International Journal of Scientific Research and Management (IJSRM), 2022)
:  A combination of metabolic heat and environmental variables causes heat stress (air temperature, humidity, air flow rate, heat radiation temperature). Sweating is induced by fluid loss through evaporation in response to heat stress. Dehydration can occur if the conditions of loss or loss of water or excessive bodily fluids and fluid intake are not restored, which can have an influence on the occupational health of outdoor workers. Analytic observational study was conducted using a Cross Sectional Study technique. All of the participants in this study were outdoor workers at parking area and security guards at a private hospital in Palembang. Using the total sampling approach, 46 samples were acquired that fulfilled the inclusion criteria but did not match the exclusion requirements. 43.5 percent of outdoor employees were exposed to heat stress. The results showed that 67.4 percent were dehydrated and 32.6 percent were not dehydrated. With a p-value of 0.009 (P